3-weekly or weekly cisplatin concurrently with radiotherapy for patients with squamous cell carcinoma of the head and neck – a multicentre, retrospective analysis - Seth Helfenstein; Oliver Riesterer; Urs R. Meier; Alexandros Papachristofilou; Benjamin Kasenda; Miklos Pless; Sacha I. Rothschild (Radiation Oncology, 2019)
Abstract Background Concurrent chemoradiotherapy with cisplatin is standard for patients (pts) with loco-regionally advanced squamous cell carcinoma of the head and neck (LA-SCCHN) and for patients with resected SCCHN with high-risk features. The standard regimen includes 3-weekly cisplatin, but weekly regimens are often used to lower toxicity. Reaching a cumulative dose of ≥200 mg/m2 cisplatin was shown being associated with improved outcome. We herein investigated cumulative dose reached and toxicities between the 3-weekly and weekly cisplatin regimens with concurrent radiotherapy. Methods Multicentre, retrospective analysis of all patients undergoing combined RCT with cisplatin treated at 3 centres in Switzerland between 06/2008 and 12/2015. Results Three hundred fourteen pts. were included (3-weekly, N = 127; weekly, N = 187). Median cumulative cisplatin dose was 200 mg/m2 (IQR 150–300) for pts. treated with a 3-weekly schedule and 160 mg/m2 (120–240) for the weekly schedule, consequently more pts. treated with a 3-weekly schedule reached a cumulative dose ≥200 mg/m2 (75.6% vs. 47.1%, p < 0.001). This association was also observed in multivariable analysis adjusted for age and sex (OR 3.46, 95% confidence interval [CI], 2.1–5.7). The 3-weekly regimen led to a higher rate of acute renal toxicity (33.1% vs. 20.9%, p = 0.022). In the landmark analysis, we could not confirm that a cisplatin dose ≥200 mg/m2 is associated with better survival (HR 1.3, 95% CI 0.8–1.9). Conclusions Significantly more patients receive a cumulative cisplatin dose of ≥200 mg/m2, when treated with a 3-weekly schedule compared to weekly dosing. The previously reported association between a cumulative cisplatin dose ≥200 mg/m2 and improved outcome could not be shown in our study.